Pengembangan SMS Gateway Sebagai Pusat Penyebaran Informasi Sekolah - Rico Andrian; Didik Kurniawan; Florencia Irena (Universitas Lampung, 2014)
Nowadays, information is no longer a complementary product but a major requairement especially in some institutions such as schools. Dissemination of information on the school system is still using paper. Dissemination of information can be facilitated by making an SMS-based information system center for announcing some school activities to parents, teachers, and students by SMS gateway as school information dissemination center. SMS gateway system is implemented by using a MySQL database, GAMMU as SMS gateway tools and programming language PHP.Keywords: Information, SMS Center, SMS Gateway, GAMMU